A diachronic study on the image construction of the “Belt and Road Initiative” in mainstream Austrian newspapers - Xianhui Li; Mei Yang (Humanities & Social Sciences Communications)
Abstract Since its introduction in September 2013, the Belt and Road Initiative (BRI) has evolved into a significant platform for international cooperation, yielding notable global outcomes. Existing research on media discourse surrounding the BRI has predominantly focused on English-speaking countries, with limited attention given to non-English-speaking nations, particularly Austria. This study employs the discourse-historical approach and a corpus-based diachronic analysis to examine the image construction of China’s BRI in Austrian mainstream newspapers over a ten-year period (2013–2023). The findings reveal a shift in Austrian media’s perception of the BRI, moving from “rational detachment” to “advocating participation” and eventually to “cautious cooperation”. The portrayal of the BRI has undergone a diachronic transformation, evolving from a “mixed positive and negative” perspective to a “positive” one and to a “mixed” stance over time. These shifts reflect the complex and evolving attitudes of Austrian media toward the BRI, revealing the interplay of cultural and geopolitical factors in shaping media discourse. This study enriches the understanding of the BRI as a significant platform for cultural exchange in the globalized world, while providing insights into the process of media discourse construction and the evolving role of media in shaping perceptions of global initiatives.